Model-Based Analysis of Costs and Outcomes of Non-Invasive Prenatal Testing for Down’s Syndrome Using Cell Free Fetal DNA in the UK National Health Service - Morris, Stephen (Public Library of Science, 2014)
BACKGROUND: Non-invasive prenatal testing (NIPT) for Down’s syndrome (DS) using cell free fetal DNA in maternal blood has the potential to dramatically alter the way prenatal screening and diagnosis is delivered. Before NIPT can be implemented into routine practice, information is required on its costs and benefits. We investigated the costs and outcomes of NIPT for DS as contingent testing and as first-line testing compared with the current DS screening programme in the UK National Health Service. METHODS: We used a pre-existing model to evaluate the costs and outcomes associated with NIPT compared with the current DS screening programme. The analysis was based on a hypothetical screening population of 10,000 pregnant women. Model inputs were taken from published sources. The main outcome measures were number of DS cases detected, number of procedure-related miscarriages and total cost. RESULTS: At a screening risk cut-off of 1∶150 NIPT as contingent testing detects slightly fewer DS cases, has fewer procedure-related miscarriages, and costs the same as current DS screening (around UK£280,000) at a cost of £500 per NIPT. As first-line testing NIPT detects more DS cases, has fewer procedure-related miscarriages, and is more expensive than current screening at a cost of £50 per NIPT. When NIPT uptake increases, NIPT detects more DS cases with a small increase in procedure-related miscarriages and costs. CONCLUSIONS: NIPT is currently available in the private sector in the UK at a price of £400-£900. If the NHS cost was at the lower end of this range then at a screening risk cut-off of 1∶150 NIPT as contingent testing would be cost neutral or cost saving compared with current DS screening. As first-line testing NIPT is likely to produce more favourable outcomes but at greater cost. Further research is needed to evaluate NIPT under real world conditions.